Enhancing the Sustainability of Concrete Mixes Utilizing Supplementary Cementitious Materials in Renewable Energy Buildings - Abdullah, Arjan Fakhrulddin; Ezuldin, Nabaz Yassen; Ahmed, Inas Mahmood; Al-Khafaji, Zainab (Engineering, Technology & Applied Science Research, 2025)
The growing emphasis on sustainable infrastructure has increased interest in Geo-Polymer Concrete (GPC) as an eco-friendly alternative to Ordinary Portland Cement (OPC). This study evaluates the mechanical performance of GPC incorporating binary combinations of Supplementary Cementitious Materials (SCMs), specifically Ground Granulated Blast Furnace Slag (GGBS), fly ash, and metakaolin. Four mixes were developed and tested for compressive, splitting tensile, and flexural strength at 7 and 28 days. The blend of slag and fly ash (G1) exhibited superior strength characteristics, achieving 41 MPa in compression, 2.75 MPa in tensile strength, and 3.85 MPa in flexural strength at 28 days. The One-way Analysis of Variance (ANOVA) confirmed statistically significant variations between the mixes. The correlation analysis revealed strong linear relationships between the compressive strength and both tensile (R = 0.93) and flexural strength (R = 0.98), suggesting that the compressive strength may serve as a practical predictor in the early-stage mix design. The enhanced performance of slag-based mixes is attributed to the improved geo-polymer gel formation and matrix densification. These findings support the use of SCM-based GPC as a sustainable and high-performance material for renewable energy infrastructure, contributing to reduced carbon emissions and more efficient resource utilization in the construction sector.